Understanding the performance of a pan-African intervention to reduce postoperative mortality: a mixed-methods process evaluation of the ASOS-2 trial. (November 2021) - Vickery, Nicola; Stephens, Timothy; du Toit, Leon; van Straaten, Dawid; Pearse, Rupert; Torborg, Alexandra; Rolt, Lucy; Puchert, Mariechen; Martin, Graham; Biccard, Bruce; ,
Abstract: Background: The African Surgical OutcomeS-2 (ASOS-2) trial tested an enhanced postoperative surveillance intervention to reduce postoperative mortality in Africa. We undertook a concurrent evaluation to understand the process of intervention delivery. Methods: Mixed-methods process evaluation, including field notes, interviews, and post-trial questionnaire responses. Qualitative analysis used the framework method with subsequent creation of comparative case studies, grouping hospitals by intervention fidelity. A post-trial questionnaire was developed using initial qualitative analyses. Categorical variables were summarised as count (%) and continuous variables as median (inter-quartile range [IQR]). Odds ratios (OR) were used to rank influences by impact on fidelity. Results: The dataset included eight in-depth case studies, and 96 questionnaire responses (response rate 67%) plus intervention fidelity data for each trial site. Overall, 57% ( n =55/96) of hospitals achieved intervention delivery using an inclusive definition of fidelity. Delivery of the ASOS-2 interventions and data collection presented a significant burden to the investigators, outstripping limited resources. The influences most associated with fidelity were: surgical staff enthusiasm for the trial (OR=3.0; 95% confidence interval [CI], 1.3–7.0); nursing management support of the trial (OR=2.6; 95% CI, 1.1–6.5); performance of a dummy run (OR=2.6; 95% CI, 1.1–6.1); nursing colleagues seeing the value of the intervention(s) (OR=2.1; 95% CI, 0.9–5.7); and site investigators' belief in the effectiveness of the intervention (OR=3.2; 95% CI, 1.2–9.4). Conclusions: ASOS-2 has proved that coordinated interventional research across Africa is possible, but delivering the ASOS-2 interventions was a major challenge for many investigators. Future improvement science efforts must include better planning for intervention delivery, additional support to investigators, and promotion of strong inter-professional teamwork. Clinical trial registration: ClinicalTrials gov NCT03853824 .